A word from our sponsor : admen, advertising, and the golden age of radio - Meyers, Cynthia B. (Fordham University Press, 2013)
This book describes how admen, advertising agencies, and sponsors shaped U.S. radio into a commercial entertainment medium from the late 1920s until the early 1950s. The author views the development of twentieth-century popular culture through the lens of the advertising and broadcasting industries, and examines the intersection of commerce and culture in American mass media.